AN ANALYSIS OF THE MORPHOSYNTAX OF VERBS IN THE BUGINESE LANGUAGE BY USING FLEX - Muhammad Nadir (Universitas Islam Negeri Alauddin Makassar, 2017)
This study will examine the morphosyntax in the Buginese language by using FLEX. The use of FLEX tool in this research is aimed to make logical linking within the verbs that are used in the syntactical context as well as to give a structural description about morphosyntactic features that define verbs in the daily communication among Buginese communities, especially who dwell the Sidenreng Rappang regency of South Sulawesi. The result will be projected in making the concordance and the compatibility of verbs as a colloquial diction. They would be identified according to affixes and clitics as well as the semantic features that assume verbs according to whether they have an objects or not. The result also will examine the basic forms of verbs in the Buginese language and their change in meaning when they are used in the different context and the different situation.